The Induction of Alpha-1 Antitrypsin by Vitamin D in Human T Cells Is TGF-β Dependent: A Proposed Anti-inflammatory Role in Airway Disease - Chen, Yin-Huai; Cheadle, Charlotte E.; Rice, Louise V.; Pfeffer, Paul E.; Dimeloe, Sarah; Gupta, Atul; Bush, Andrew; Gooptu, Bibek; Hawrylowicz, Catherine M. (Frontiers in Nutrition, 2021)
Background: Vitamin D upregulates anti-inflammatory and antimicrobial pathways that promote respiratory health. Vitamin D synthesis is initiated following skin exposure to sunlight, however nutritional supplementation can be required to address deficiency, for example during the winter months or due to cultural constraints. We recently reported that 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) treatment induced alpha-1 antitrypsin (AAT) expression in CD4+, but not CD8+ T cells, with evidence supporting an immunoregulatory role. Research Question: To understand the relationship between vitamin D, lung AAT levels and T lymphocytes further we investigated whether TGF- is required as a co-factor for 1,25(OH)2D3-induced upregulation of AAT by vitamin D in CD8+ T cells in vitro and correlated circulating vitamin D levels with lung AAT levels in vivo. Results: 1,25(OH)2D3 in combination with TGF-β1 increased AAT expression by CD8+ T cells, as well as VDR and RXRα gene expression, which may partly explain the requirement for TGF-β. CD4+ T cells may also require autocrine stimulation with TGF-β as a co-factor since 1,25(OH)2D3 was associated with increased TGF- bioactivity and neutralisation of TGF-β partially abrogated 1,25(OH)2D3-induced SERPINA1 gene expression. Neither CD4+ nor CD8+ T cells responded to the circulating vitamin D precursor, 25-hydroxyvitamin D3 for induction of SERPINA1, suggesting that local generation of 1,25(OH)2D3 is required. Transcriptional gene profiling studies previously demonstrated that human bronchial epithelial cells rapidly increased TGF-β2 gene expression in response to 1,25(OH)2D3. Here, human epithelial cells responded to precursor 25(OH)D3 to increase bioactive TGF-β synthesis. CD8+ T cells responded comparably to TGF-β1 and TGF-β2 to increase 1,25(OH)2D3-induced AAT. However, CD8+ T cells from adults with AAT-deficiency, homozygous for the Z allele of SERPINA1, were unable to mount this response. AAT levels in the airways of children with asthma correlated with circulating 25(OH)D3. Conclusions: Vitamin D increases AAT expression in human T cells and this response is impaired in T cells from individuals homozygous for the Z allele of SERPINA1 in a clinic population. Furthermore, a correlation between circulating vitamin D and airway AAT is reported. We propose that vitamin D-induced AAT contributes to local immunomodulation and airway health effects previously attributed to vitamin D.